Lee Hwok Aun and Christopher Choong, eds. Inequality and Exclusion in Southeast Asia: Old Fractures, New Frontiers. Singapore: ISEAS-Yusof Ishak Institute, 2021. 344 pp. - Abletis, John N. (Archīum Ateneo, 2022)
Excerpt from Book Review: Inequality has been a significant concern for policy makers, academics, development workers, and the general public because it affects political stability, the enjoyment of human rights, efficient utilization of national resources, human and economic development, and on a more personal level, the life chances of individuals. Hence, any attempt that aids in understanding how inequality and its various determinants and consequences work in society is a welcome contribution not just to scholarship on inequality and stratification but also to efforts in mitigating their multi-layered and interacting effects. It is in this light that one can appreciate the book edited by Lee Hwok Aun and Christopher Choong, Inequality and Exclusion in Southeast Asia: Old Fractures, New Frontiers.